SISTEM IMPLEMENTASI RENCANA AKSI KEBIJAKAN PENGEMBANGAN INDUSTRI HILIR KELAPA SAWIT DI INDONESIA - Syekh Farhan Robbani; Idqan Fahmi; Gendut Suprayitno (School of Business, Bogor Agricultural University (SB-IPB), 2015)
Palm oil industry is one of the important industries in Indonesia, but the development only focuses on upstream industry. The government establishes downstream palm oil industry is once of the priorities development industry and will be mainstay industry in future by issues Regulation of Minister Industry No 13/2010 to support it. The aims of this study are to analyze the action plan’s implementation of downstream palm oil industry’s policy and the priority of action plan’s policy implementation based on Regulation of Minister Industry No. 13/2010. This study uses literature review, in-depth interview and questionnaire method to gather opinions from the experts and practitioners, and then analyzed using Analytical Network Process (ANP). The results of this study show that the implementing of action plan the policy of downstream palm oil industry should use priority in improving infrastructure and investment process. Especially availability public facilities such as highway, electricity generator, treatment water installation and support in pro-investment policy. The most important stakeholder is a role of central government be at the facilitators for developing downstream palm oil industry, especially on policy and support system The main recommendation of action plan implementation is improving support system on building public infrastructure process and investment like land clearance policy, investment tax policy, funding scheme and cooperation on development between state-owned corporation and private corporation.Keywords: Analytical Network Process (ANP), downstream palm oil, implementation policy analysisABSTRAKIndustri kelapa sawit merupakan industri penting di Indonesia, namun pengembangannya masih berfokus kepada industri hulu. Pemerintah menetapkan industri hilir kelapa sawit sebagai salah satu industri prioritas yang akan dikembangkan dan menjadi industri andalan masa depan dengan menerbitkan Peraturan Menteri Perindustrian No 13 tahun 2010 untuk mendukung tujuan tersebut. Tujuan penelitian ini adalah untuk menganalisa implementasi rencana aksi kebijakan pengembangan industri hilir kelapa sawit dan memilih prioritas rencana aksi yang diutamakan dalam Permenperin no 13 Tahun 2010. Metode penelitian ini menggunakan penelitian terdahulu, wawancara mendalam dan kuisioner dari ahli atau praktsi, selanjutnya dianalisis menggunakan analisis proses jaringan (ANP). Hasil penelitian menunjukan implementasi rencana aksi kebijakan pengembangan industri hilir kelapa sawit perlu memprioritaskan perbaikan proses infrastruktur dan investasi. khususnya ketersediaan fasilitas umum meliputi jalan raya, pembangkit listrik dan pengelolaan air bersih serta mendukung kebijakan pro-investasi. Peran terpenting pemangku kepentingan adalah peran pemerintah pusat yang menjadi fasilitator bagi pengembangan industri, khususnya terkait kebijakan dan sistem pendukungnya. Rekomendasi utama pengembangan industri hilir kelapa sawit adalah memperbaiki sistem pendukung dalam proses pembangunan infrastruktur dan investasi seperti kebijakan pembebasan lahan, kebijakan pajak investasi, skema pembiayaan dan kerjasama pembangunan antara BUMN dan swasta. Kata kunci: analisis proses jaringan (ANP), industri hilir kelapa sawit, analisis implementasi kebijakan